Jaw Cysts: A Retrospective Study in a Turkish Subpopulation - Emre Haylaz; Murat İçen; Çiğdem Şeker; Gediz Geduk (Cumhuriyet University, 2022)
Objectives: Cysts seen in the jaws may be odontogenic or non-odontogenic, depending on the tissue of origin. Although there are different methods to diagnose these lesions, histopathological examination of tissue biopsy of the lesion is accepted as the 'gold standard' in cases where the diagnosis is insufficient. Although there are different methods to diagnose these lesions, histopathological examination of tissue biopsy of the lesion is accepted as the 'gold standard' in cases where the diagnosis is insufficient. Materials and Methods: Pathology results of 436 patients who applied to Zonguldak Bülent Ecevit University Faculty of Dentistry, Oral and Maxillofacial Radiology Clinic between 2016-2021 for any reason and underwent biopsy were retrospectively scanned using digital archives. While classifying the cyst, the criteria published by the World Health Organization (WHO) in 2017 were taken into account. Obtained results were recorded for statistical analysis. SPSS 22.0 Software Package Program (SPSS 22.0 Software Package Program, Inc. Chicago, IL, USA) was used as statistical software in the study. Results: Of the 436 patients included in the study, 250 (57.3%) were male and 186 (42.7%) were female. The ages of the patients ranged between 7 and 82 years, and the mean age of the patients was 35.5±15.8. As a result of the findings, it was determined that the most common cysts were radicular cysts (53.7%). Radicular cysts were most commonly located in the posterior mandible and anterior maxilla anatomically. Conclusions: In addition to clinical and radiological examination, histopathological examination of biopsy samples taken from tissues is of great importance in the correct diagnosis and treatment planning of jaw cysts.